Соціологічна репрезентація образів чоловіка й жінки в національному медійному просторі - Орлов, Андрій Володимирович; Орлов, Андрей Владимирович; Orlov, Andrii V.; Хімченко, Олександра Анатоліївна; Химченко, Александра Анатольевна; Khimchenko, Oleksandra A. (Східноєвропейський національний університет імені Лесі Українки, 2015)
Послуговуючись основними концептуальними моделями гендерних стереотипів у рекламі та авторським емпіричним дослідженням (контент-аналіз телевізійної реклами національного медіапростору («1+1», «ICTV», «Новий канал») протягом квітня 2015 р.), визначено, що вона скерована здебільшого в бік жінки як основного споживача. Серед жіночих гендерних образів переважають моделі бізнес-вумен, домогосподарки та мами, а чоловічих – моделі бізнесмена й тата. This article analyzes one aspect of gender stereotyping of the public sphere of society, namely, gender images, which are transmitted by means of television advertising. Carried out a theoretical review of the issue, highlighted and conceptualize basic models of gender stereotypes in advertising. Specificity of building models gender stereotypes in the context of the study directions post-modern communication. The results of content analysis of television advertising national TV channels («1+1», «ICTV» and «New Channel») based on the use of mechanical, cluster sampling method and a typical representative. According to the results of empirical analysis provides a comparative analysis of the advertising context, identified the most common gender images, specifics of their use and their associated attributes. Identify cultural and social component of television advertising. It was determined that the advertising is directed primarily toward women as the main consumer. Among the female gender images is dominated by models businesswomen, housewives and mothers, and men - businessman and a model father.
Sociological Studies of Stereotypes Men and Women in the National Media Space
Keywords: гендерний стереотип; гендерна модель реклами; маскулінність; фемінність; gender stereotype; gender-advertising model; masculinity; femininity